Analisis Keterampilan Pemecahan Masalah Peserta Didik Pada Pembelajaran Biologi Kelas XI SMA Negeri di Kabupaten Sleman - Avi Dwi Ayunda; Himmatul Hasanah; Nur Aeni Ariyanti (Postgraduate, University of Mataram, 2024)
Problem-solving skills are considered essential for students to have because they can help students make appropriate, careful, systematic, logical decisions and weigh various viewpoints. High school students must have problem-solving skills because biology subjects are developed through analytical, inductive, and deductive thinking to solve problems related to nature. This research aims to determine students' problem-solving skills in class XI biology learning at State High Schools in Sleman Regency. This research is a type of descriptive research using a survey approach. The population in this study were all Sleman Regency State High Schools, namely 17 schools with a sample of 9 schools so the subjects in this study were 249 students. Research subjects were selected using probability sampling with cluster sampling techniques. The data collection technique uses tests in the form of problem-solving questions. The results of the research show that the level of problem-solving skills of class XI students at state SMA Sleman Regency was in the medium category with a percentage of 43.21%. The percentage of each indicator, namely understanding the problem, is 65.8% in the capable category, evaluating alternatives is 37% in the less category, and creating a problem-solving plan is 29% in the less category.